Structural and Metabolic Effects of Obesity on the Myocardium and the Aorta. - Rider, O; Lewis, A; Neubauer, S (S. Karger AG, 2014)
Obesity per se is a recognized risk factor for cardiovascular disease exerting independent adverse effects on the cardiovascular system. Despite this well documented link, the mechanisms by which obesity modulates cardiovascular risk are not well understood. Obesity is linked to a wide variety of cardiac changes, from subclinical diastolic dysfunction to end stage systolic heart failure. In addition, obesity causes changes in cardiac metabolism that make ATP production and utilization less efficient producing functional consequences that are linked to the increased rate of heart failure in this population. This review focuses on the cardiovascular structural and metabolic remodelling that occurs in obesity with and without co-morbidities and the potential links to increased mortality in this population. © 2014 S. Karger GmbH, Freiburg.